Students' Anxiety in Oral Presentations: Factors and Strategies at UIN Raden Intan Lampung - Riyadi, Sugeng; Suryawati, Sri Suci; Aziz, Rizal (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This study examines the level of speaking anxiety, identifies contributing factors, and explores strategies to address speaking anxiety during oral presentations in speaking classes among fourth-semester students at UIN Raden Intan Lampung. A qualitative descriptive design was employed, involving 55 English Department students. Data were collected using questionnaires and semi-structured interviews. The Foreign Language Classroom Anxiety Scale (FLCAS), developed by Horwitz et al. (1986), was modified and used to assess Foreign Language Anxiety (FLA). This 33-item, 5-point Likert scale measures students' language anxiety. Results indicate that speaking anxiety is prevalent among the students, particularly during oral presentations, with an average FLCAS score of 36.218. Interviews with six students, representing both low and high anxiety levels, revealed several factors contributing to speaking anxiety. These include negative thinking, lack of preparation, bad experiences, low ability, low confidence, fear of making mistakes, and physical conditions. To mitigate anxiety, students suggested strategies such as thorough preparation, managing negative thoughts, increasing self-confidence, using relaxation techniques, and improving language skills. The findings emphasize the importance of addressing speaking anxiety in EFL classrooms. Educators can create a supportive environment, incorporate activities to build confidence, and teach anxiety management strategies. Institutions should consider workshops on public speaking and anxiety reduction. Additionally, integrating frequent oral practice and personalized feedback into teaching methods can enhance students' speaking performance and reduce anxiety effectively.